2011
DOI: 10.1021/jo102555r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-Methoxyazetidines via an Aziridine to Azetidine Rearrangement and Theoretical Rationalization of the Reaction Mechanism

Abstract: The synthetic utility of N-alkylidene-(2,3-dibromo-2-methylpropyl)amines and N-(2,3-dibromo-2-methylpropylidene)benzylamines was demonstrated by the unexpected synthesis of 3-methoxy-3-methylazetidines upon treatment with sodium borohydride in methanol under reflux through a rare aziridine to azetidine rearrangement. These findings stand in contrast to the known reactivity of the closely related N-alkylidene-(2,3-dibromopropyl)amines, which are easily converted into 2-(bromomethyl)aziridines under the same rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 102 publications
1
15
0
Order By: Relevance
“…The calculated energy barrier for 5 → 9 is 64.7 kJ mol −1 higher than the corresponding barrier for cyclodehydration 5 → 8. This is in line with earlier studies showing that the energy barrier for azetidine ring formation in aminoalcohols 48 or aminohalides 49 can be quite substantial (up to 200 kJ mol −1 ).…”
Section: Cyclodehydration Reactions Ofsupporting
confidence: 93%
“…The calculated energy barrier for 5 → 9 is 64.7 kJ mol −1 higher than the corresponding barrier for cyclodehydration 5 → 8. This is in line with earlier studies showing that the energy barrier for azetidine ring formation in aminoalcohols 48 or aminohalides 49 can be quite substantial (up to 200 kJ mol −1 ).…”
Section: Cyclodehydration Reactions Ofsupporting
confidence: 93%
“…A novel aziridine to azetidine rearrangement protocol has been developed by the conversion of 2-bromomethyl-2-methylaziridines 37. 36 Treatment of aziridines 37 with sodium borohydride is suggested to form a bicyclic intermediate 38 that undergoes reaction with methanol to form the azetidines 39 (Scheme 13). The cyclization of aziridines 37 to the bicyclic intermediate 39, which is in contrast with the well-known chemistry of 2-(bromomethyl)aziridines 37 bearing no additional substituent at C-2-position, was interpreted as the Thorpe-Ingold effect due to the gem-disubstitution at the aziridine carbon atom, resulting in a more favorable geometric positioning of the nucleophilic nitrogen atom with respect to the halogenated carbon atom.…”
Section: Synthesis Of Azetidinesmentioning
confidence: 99%
“…The proposed pathway concurs with the previously reported synthesis of 3-methoxy-3-methylazetidines 3 (R 1 = CH 2 Ar, R 2 = Me, Scheme 3) comprising the smooth ring expansion of 2-bromomethyl-2-methylaziridines 2 via bicyclic aziridinium intermediates 14 upon heating in methanol in the presence of NaBH 4 . 7 In the same study, it has been shown that 3-methoxy-3-methylazetidines 3 can also be obtained starting from 3-bromoazetidines 4 applying the same reaction conditions (NaBH 4 , MeOH, Δ). The latter transformation served as a starting point to thoroughly investigate the synthetic potential of 3-bromo-3-methylazetidines for the preparation of novel 3-substituted azetidines.…”
Section: %mentioning
confidence: 91%
“…7 Until then, the peculiar rearrangement of 2-(halomethyl)aziridines to 3-haloazetidines had been observed in the literature in only two specific cases. MeOH, Ar Scheme 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation